Urban design through landscape architecture - Albert Fekete (Anales del Instituto de Arte Americano e Investigaciones Estéticas "Mario J. Buschiazzo")
Hungarian Landscape architecture has become an independent discipline substantial in both the contemporary open space design and urban design in Hungary. Challenges of the global climate change, the issues of urban liveability and sustainable rainwater management, have played an inevitable role in self-definition and acknowledgment of the landscape architecture profession, same way as the changing of social context and sensitivity towards issues of environmental quality.